Physiologic function of mediastinum space. (October 2022) - Azimi, Ghasem; Bozorgmehr, Rama; Sattari, Parastesh; Azimi, Ali; Azimi, Hossein; Marzban-Rad, Saeid
Abstract: The mediastinum forms the central part of the thoracic cavity that is surrounded by pleural space on the two sides, thoracic vertebrae at the posterior, thoracic inlet on the top, and diaphragm at the bottom. It encompasses cardiopulmonary organs and organ systems. Pathological dysfunction or deformity in any part of the mediastinum can have adverse cardiovascular and respqiratory effects. Pectus excavatum and pectus carinatum are the most common congenital chest deformities that are characterized by sternal depression and protuberance of the sternum, respectively. Together, these account for 90% of chest wall deformities. Patients are known to be represented with respiratory distress and cardiovascular dysfunction. The aim of the review article is to present the anatomical and physiological role of the mediastinum in association with important parts of the thoracic cavity and pathological dysfunction of the mediastinum (cardiopulmonary system) due to pectus excavatum and pectus carinatum. Highlights: Mediastinum forms the central part of thoracic cavity that is surrounded by pleural space. PC and PE are structural chest deformities. Chest deformation by pressing on the chin causes coughing, stridor, dyspnea and exacerbation. Clinical symptoms along with inflammation that requires urgent medical treatment.